Aspirations and accommodations for students with disability to equitably access higher education: a systematic scoping review - Bartolo, Paul A.; Borg, Michelle; Callus, Anne-Marie; De Gaetano, Alistair; Mangiafico, Marchita; Mazzacano D’Amato, Edward; Sammut, Carmen; Vella Vidal, Ramona; Vincent, Jonathan (Frontiers in Education, 2023)
Several international conventions have recognized the importance of equal access to higher education on the basis of 'capacity'. However, inequalities persist for various groups. This paper presents a systematic scoping review of studies on the aspirations and access needs of students with disability, medical and mental health conditions to equitably participate in tertiary education. A search of ERIC, PsycINFO and Web of Science databases identified 133 relevant research articles from across the world covering the experiences of students with all types of disability. A thematic analysis identified three main themes and thirteen subthemes. Firstly, the findings showed that a crucial component of the student higher education experience was the development of their own self-identity, addressing stigma and enhancing self-advocacy skills, autonomy, and career prospects; secondly, the studies described how students struggled for full membership in the university community, calling for a transformation of university physical, social and teaching environments for them to access and participate in academic and social activities; and thirdly, the analysis showed that students valued individual accommodations in both coursework and assessment. These findings constitute a newly comprehensive framework for inclusive tertiary education systems and individual accommodations which is grounded in empirical research from a wide variety of contexts. This can serve higher education institutions to develop policy and procedures to ensure equitable participation of students with disability. *Lucas, R., Cage, E., and James, A. I. (2018a). Expectations of the university to post-graduation transition of students with mental health conditions. British Psychological Society.